Effect of Sisal Fiber Surface Treatment on Properties of Sisal Fiber Reinforced Polylactide Composites - Zhaoqian Li; Xiaodong Zhou; Chonghua Pei (International Journal of Polymer Science)
Mechanical properties of composites are strongly influenced by the quality of the fiber/matrix interface. The objective of this study was to evaluate the mechanical properties of polylactide (PLA) composites as a function of modification of sisal fiber with two different macromolecular coupling agents. Sisal fiber reinforced polylactide composites were prepared by injection molding, and the properties of composites were studied by static/dynamic mechanical analysis (DMA). The results from mechanical testing revealed that surface-treated sisal fiber reinforced composite offered superior mechanical properties compared to untreated fiber reinforced polylactide composite, which indicated that better adhesion between sisal fiber and PLA matrix was achieved. Scanning electron microscopy (SEM) investigations also showed that surface modifications improved the adhesion of the sisal fiber/polylactide matrix.